How does self-efficacy, learner personality, and learner anxiety affect critical thinking of students - Fu, Jing; Ding, Yi; Nie, Kaihua; Zaigham, Ghulam Hussain Khan (Frontiers in Psychology, 2023)
The goal of critical thinking for students is to help them learn how to think critically and systematically so they can solve problems and make informed decisions. It aids students in developing their capacity for independent thought, allowing them to generate their own conclusions and base those decisions on facts and evidence. Therefore, one of the key goals of this study was to explore the factors affecting critical thinking of English as foreign language (EFL) learners. This article used social cognitive theory (SCT) to investigate how personal and cognitive factors affect EFL learners’ critical thinking. Data from 305 Chinese EFL learners were collected online, and structural equation modeling (SEM) was used to evaluate the data. The results showed that metacognitive learning strategies (MLS) were positively related to critical thinking and that self-efficacy, self-oriented learning perfectionism, and learner anxiety were significantly related to MLS. Moreover, MLS mediated the link between self-efficacy, self-oriented learning perfectionism, learner anxiety, and critical thinking. The findings further indicated that learner proactivity moderated the association between MLS and critical thinking. By applying social cognitive theory to examine the variables influencing EFL learners' critical thinking, this study adds uniqueness. It does this by emphasizing the moderating influence of learner proactivity and the mediating function of metacognitive learning strategies. The findings of the research have significant ramifications for educators since they emphasize how vital it is to support metacognitive strategies for learning in order to improve EFL learners' critical thinking abilities. Additionally, to create an atmosphere that is favorable for the development of critical thinking skills in EFL education, policymakers should think about implementing support systems and interventions that focus on learner anxiety, learner proactivity, and self-efficacy.